Measuring ball spin off a tennis racket - Goodwill, S.; Douglas, J.; Miller, S.; Haake, S. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
A series of experiments were carried out in which a spinning tennis ball was projected obliquely at a head clamped racket. In each experiment a different string was used in the racket frame. An automated image analysis algorithm was used to measure the velocity and spin of the ball. It has been found that, for the majority of impacts, the magnitude of the ball rebound spin was dependent on string stiffness. It has been concluded that the string stiffness influences the magnitude of stringbed lateral movement during impact. This differing magnitude of lateral string movement, in turn, influences the amount of ball rebound spin.